Factors Influencing Parent’s Intention To Buy Early Childhood Educational Toys - Achelia Setiani; Indra Cipta Guna Setia Permana; Kezia Dara Euodia; Nuraini Nuraini; Priska Paramita Pradipta; Istijanto Istijanto (Jurnal Riset Bisnis, 2023)
This study aims to examine the factors that influence the parents’ intention to buy early childhood educational toys for their children by extending the theory of planned behavior as a base of explanation. The research method was a survey using online questionnaires with convenience sampling to 262 parents who have 0-6 years old children living in Indonesia. The analysis methods were descriptive statistics, exploratory factor analysis, and multiple regression. The results show that the most significant factor influencing the parent’s intention to buy is the perceived behavioral control, followed by attitude, subjective norms, perceived value for money, and perceived product quality. However, perceived product risk does not significantly affect the intention to buy early childhood educational toys. The findings of this research contribute to the literatures on the parents’ purchase behavior by extending the theory of planned behavior. In addition, this study also helps marketers, producers, and distributors of early childhood educational toys to define a better strategy in approaching parents to buy the products for their children. Additionally, toy designers or educators can use the result to consider the designs that satisfy parents as decision-makers. This study was limited to Indonesian parents, so the result cannot be generalized for a wider market. Thus, future research can capture more diverse categories, additional variables, and social groups.